Casework with psychiatric patients : an empirical study of treatment tendencies - Chinkanda, Esther Nozizwe (My University, 1981)
Refer to the document
Thesis (M.A. (Social Work)) -- University of the North, 1981
Keywords: Psychiatric patients; Social case work; Psychiatric treatment; Psychiatric social work; Psychiatric hospital patients